Biblioteki kościelne w aspekcie kanonicznym - Adamczyk, Jerzy (Archiwa, Biblioteki i Muzea Kościelne, 2013)
This article is devoted to church libraries in the canonic aspect. Church library is the institution that collects, prepares and makes collections of books and manuscripts, which are the property of church institutions, available to readers. In the first part of this article the definition of the church library has been suggested, which is the organized collection of manuscripts, printing or elaborations and other resources, which aims at imparting texts and paintings, which is owned by approved or erected in canonic system institutions. Afterwards, the problem of library collection has been presented, which is the collection of manuscripts, printing or elaborations and other resources, as well as the issue of the content of these resources. The grading of libraries according to the criterion of the size of the collection of books and manuscripts has also been done. The attention was directed to the problem of maintaining and enlarging the library collection, too. A lot of attention was given to the organisation of church libraries that not only are the collections of books and manuscripts, but also collect, prepare, make available and inform about collections of books and manuscripts. Within the scope of the organization of church libraries the issue of library, rental and reading room workers has been discussed, as well as the appropriate indemnification of the collection.